Democracia digital nos estados brasileiros: uma análise da governança eletrônica a partir de elementos de participação e deliberação - Rodrigues, Izabela França (2017)
Advances in the field of information and communication technologies (ICT) have affected society and enable reconfigurations in the forms of relations between citizens and governments, favoring new possibilities. Alongside this, in the last decades debates about democratic quality have broadened, postulating the extension of social participation, as in contemporary theoretical developments along the lines of participatory and deliberative democracy. In this context, new forms of social participation are presented either in the civil society and in the public sphere, or in the field of institutionalized participation. In the Brazilian case, the forms of institutionalized participation were expanded: new legal frameworks were set up for the democratization of the State and its relations with society, and a participatory infrastructure was created with a multiplicity of new participatory institutions with designs and purposes different. In this context, the term governance and its variations have been widely used, highlighting the notion of participatory governance, which emphasizes the possibilities of social participation and e-governance. Several potentialities have been associated with e-governance, pointing out that through ICTs the government could become more accessible to citizens, overcome democratic deficits and expand democracy by adopting participatory and deliberation practices in a virtual environment. Thus, the research aims to analyze the initiatives of digital democracy in the Brazilian states and the Federal District, through its electronic websites, and to verify what are the democratic possibilities of these initiatives. To do so, we started with the theoretical revision of the main democratic currents, ending in the deliberative and participatory currents, indicating, the instances and practices of participation in the contemporary Brazilian context. Secondly, the notions of governance, participatory governance, governance and e-governance were discussed, and models of approach and analysis in this field were examined. From this review, an analytical model was built, encompassing 22 criteria divided into 4 different interfaces: informational, interlocution, institutional and advisory and deliberative. The application of the analytical model and evaluation has identified that most of the States grant to its portal a purely informative character and there is a heterogeneous use by the state public administrations of the potential of the ICTs in offering participation and deliberation practices. The investigation of the characteristics of the mechanisms of participation and deliberation allows the systematization of different patterns of opportunities offered, as well as the evaluation of the degree of use of the ICTs available to the state public administrations.